The Influence of Principal’s Managerial Competencies and Teachers’ Performance on the Quality of the Graduates - Putri Ajri Asadera; Rohana Rohana; Sri Wahyu Indrawati (Journal of Social Work and Science Education, 2026)
This study aimed to determine and analyze the partial and simultaneous influence of principal managerial competence and teacher performance on graduate quality in public junior high schools within Tebing Tinggi District. Employing a quantitative ex post facto approach, data were collected via questionnaires and documentation from a sample of 135 teachers. Analysis was conducted using the SPSS program. The analysis concluded that: (1) principal managerial competence significantly influences graduate quality; (2) teacher performance significantly influences graduate quality; and (3) both factors together have a significant simultaneous influence on graduate quality. This study provides empirical validation of a combined leadership-instructional framework, simultaneously testing the direct and collective impact of both administrative and pedagogical variables on educational outcomes in a specific regional context. Findings suggest that school improvement initiatives should integrate targeted leadership development for principals with continuous teacher performance enhancement programs to effectively elevate graduate standards. The research offers a validated model for stakeholders, emphasizing that synergistic improvement in school management and classroom instruction is critical for advancing educational quality.